Parathyroid carcinoma with contralateral subcutaneous and breast recurrences: A rare presentation. Issue 5 (21st December 2015) - Agarwal, Shipra; Kumar, Tarun; Sharma, Mehar C; Damle, Nishikant A.; Gandhi, Ajeet Kumar
Abstract: Background: Parathyroid carcinoma is extremely rare. Correct preoperative and even histopathological diagnosis may be difficult owing to the deceptively bland cytoarchitectural features, especially when presenting with localized disease. Recurrence/metastases developing years later then make the malignant nature obvious. Methods and Results: We present here an unusual case of a 32‐year‐old patient with carcinoma of the left upper parathyroid gland, initially diagnosed as parathyroid adenoma, treated with endoscopic left parathyroidectomy, and later developing subcutaneous metastatic nodules over the medial end of the right clavicle and right anterior chest wall, followed by a right breast deposit. The recurrences, especially subcutaneous ones, were probably secondary to tumor seeding along the track of insertion of the endoscope. Conclusion: Involvement of subcutaneous tissue and the breast in parathyroid carcinoma is extremely rare. The case is being reported for its uniqueness along with a discussion of possible appropriate course of management, which may have averted the aggressive clinical course of the disease. © 2015 Wiley Periodicals, Inc. Head Neck 38: E115–E118, 2016